Nanometer Thermal Conductivity Mapping Using Laser-based Scanning Thermal Microscopy. Issue 1754 (24th March 2015) - Goeckeritz, Jeremy; Aden, Gary; Chand, Ami
ABSTRACT: A new measurement technique using a cantilever probe with an integrated thermal sensor is investigated for measuring thermal conductivity at the nanometer scale. The probe is used in a configuration wherein the laser from an atomic force microscope (AFM) heats the tip of the probe above ambient temperature. Heat is transferred from the probe to a sample based on the thermal conductivity of the sample. The heat flow creates a temperature change, as small as 0.01 °C, which is detected by the thermal sensor. The measurement technique presented offers a simple and effective method for mapping the thermal conductivity of a number of materials. We explore the ability of the technique to map silicon oxide on silicon, carbon fibers and gold nanoparticles. Analysis shows that the technique can be used to produce images with a thermal resolution surpassing 25 nm.